P6 Temporal relationships between lung cancer MDT recommendations and final outcomes. (14th November 2013) - Shah, K; Fairclough, L; Sundar, R; Taggart, SCO
Abstract : Introduction and Objective: A previous study [1] has identified a discordancy rate of 33% between MDT treatment decision and actual treatment given to patients not suitable for best supportive care. The Northwest Sector Lung Cancer MDT (SMDT) provides recommendations for treatment for approximately 700 new diagnoses/year attending the Salford, Wigan and Bolton catchment area. The Salford Service is centralised around the Lead Clinician who assesses and refers >90% of patients to SMDT (c.f. <50% Wigan & Bolton). A detailed proforma is completed for each patient detailing performance score, co-morbidity and all diagnostic data. This study sets out to determine the temporal rates of discordance between SMDT recommendations and actual treatment pursued for Salford and Wigan. Method: Using a 1:2 random selection of all patients from Salford & Wigan diagnosed in 2011 and 2012, the hospital notes were examined to identify the SMDT recommendation and subsequent treatment received by the patient. Patients referred for Best Supportive Care were excluded. Any discordance was further explored by review of the notes. Results: The study identified a total of 441 patients; 213 (Salford) and 228 (Wigan). The discordance rates for Salford were 8% (2011), 12.8% (2012) & 10.4% (combined) c.f. 26.9% (2011), 36.9% (2012) and 32.4% for Wigan. The overall SMDT discordancy rate was 17.7% (2011), 27.0% (2012) & 19.9% (combined). Discordance occurred most commonly due to co-morbidity health concerns (44.6%), patient wishes (15.7%) and as a result of new clinical information becoming available (27.7%). Conclusions: SMDT recommendations are dependent on a detailed knowledge of patient wishes, co-morbidity and stage of disease. Discordance reflects weaknesses in patient assessment prior to referral to SMDT. Centralisation of assessment before referral to SMDT is associated with improved and acceptable discordancy rates. We recommend assessment by a dedicated Lung Cancer Clinician ahead of referral to SMDT. Reference: Pemberton L et al. Do treatment decisions made at lung cancer multi-disciplinary team meetings (MDTs) reflect the actual treatment given in practice? Lung Cancer, Volume 79, Supplement 1, January 2013, Page S36.